OPTIMASI PRODUKSI EMPAT VARIETAS JAGUNG HIBRIDA DI KERTOSONO, KABUPATEN NGANJUK - sutardjo, sutardjo; Nawfetrias, winda (Jurnal Sains dan Teknologi Indonesia, 2012)
Maize hybridization system would help Indonesia to become a maize exporter. But the development of maize hybrids in Indonesia is seemed too slow, this impacting in national maize production, which was only 13 million ton per year in 2003. In 2009, the maize hybrid has been planted in about 54% of maize yields. Fertilizing maize is on the most essential and critical parts about growing maize. The objective of the study was to obtain the maximum dosage of composed fertilizer for the highest productivity among four hybrids maize variety in dependingsoil type. The result showed that the prospecting hybrid variety of BI-1 has a maximum production yield of 7.7 ton/ha at the level of fertilizer 1,200 kg/ha and it was only 6.3 ton per ha at zero level fertilizer. Amount of 7.4 ton/ha was achieved by BI-3 maize hybrid at the level of 1,200 kg/ha fertilizer, where those only 5.8 ton/ha at the zero level of fertilizer. The highest productivity was archived by BI-4 where it was 7.1 ton/ha at zero level fertilizer and the highest production yield of 9.2 ton/ha at 900kg/ha of fertilizer, but it was decrease at the level of 1,200 kg/ha fertilizer. Maize variety of DK979 achieved highest productivity of 8.6 ton/ha at 1,200 kg/ha fertilizer and 5.8 ton/ha at zero level fertilizer.